A REVIEW OF GUNJA (ABRUS PRECATORIUS. LINN) ON BOTH ASPECT OF MEDICINE AS WELL AS POISON - Karpurashetti, Nivedita B.; Hiremath, S. K.; Manjulabai, K. H.; Karoshi, Shrutika (Asian Journal of Pharmaceutical Research and Development, 2013)
Poisons are the toxic substances which are known to the mankind since ages. Each system of Medicine has its own approach towards Visha. Though the poisons are known harmful substances but in Ayurveda that drugs are utilizing them with a special procedure called Shodan which turn them into potent medicine by removing its toxic effects. Charaka says even the poisonous drug becomes nectar when we use it in a suitable way and also a good medicine may become poisonous when we use it in an improper way. So having a depth knowledge regarding this plant will give more therapeutic effects. The success of the treatment depends upon appropriate Shodhana, dose, mode of administration, Anupaana and Vyaadhi Avastha. But Due to improper Shodhana’s and inexperienced physicians, many toxic effects, or even death may prevail. Gunja is one Upavisha having abundant therapeutic values. With proper Shodhana and administration, it can be used in treating many diseases. Hence the present paper reviews about the potential toxic qualities and therapeutic utilities of the Gunja in Ayurveda.